Research Development on Drug Resistance in Sepsis in Critically ill Patients: a Global Bibliometric Analysis (Revista de Medicina Clinica, 2024)
Introduction: Drug resistance is a priority in public health and global health. In critically ill patients, drug resistance is a strong predictor of high mortality. To date, scientific development and patterns of global research on drug resistance in sepsis in critically ill patients are unknown. Methods: A bibliometric study using Scopus as a data source. The R package bibliometrix was used to visualize the results. Results: 3323 articles were included, published between 1972 and 2024. Among these, 79% (n= 2524) correspond to articles with primary data, followed by reviews with 15% (n= 523). International collaboration was 16.82%, and annual scientific growth was 7.73%. Clinical research, cross-infection, bacteremia, antibacterial agents, and middle-aged are the most used keywords. In the last 5 years, cross-infection, bacteremia, and the elderly have been the most popular topics. The United States has the largest collaboration network. Apart from Mexico and Brazil, no other Latin American country was identified as standing out in international collaboration. Conclusions: A gradual growth in scientific development of drug resistance in sepsis was evidenced, with a notable rise in recent years, focusing essentially on clinical research testing antimicrobial agents in the middle-aged and elderly population. In Latin America, participation in collaborations was very low compared to other continents. These data can be used for the analysis and interpretation of patterns and research gaps.
Keywords: Drug Resistance; Sepsis; Critical Illness; Biomedical Research; Bibliometrics